2001
DOI: 10.1021/ic010104q
|View full text |Cite
|
Sign up to set email alerts
|

Tricyclohexylphosphine Derivatives of Bis(2,6-difluorophenoxide)cadmium:  A Solution and Solid-State NMR Study

Abstract: The synthesis of Cd(O-2,6-F2C6H3)2(PCy3)2 has been achieved by the reaction of Cd[N(SiMe3)2]2 and 2,6-difluorophenol in THF in the presence of 2 equiv of tricyclohexylphosphine, and its distorted tetrahedral structure has been established by X-ray crystallography. Comparison of the solution and solid-state 113Cd NMR spectra of this derivative suggest that a facile solution equilibrium exists between it and its dimeric monophosphine analogue and free PCy3. At ambient temperature, the equilibrium lies strongly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…4). 35,38 Going down with the temperature we observed an upfield shift of cadmium resonance with the simultaneous broadening of the resonance signal in both presented spectra. However, we were not able to measure separate signals of A and B even at 90°C ( Fig.…”
Section: 5-dimethylpyridine) B and The Reaction Of Bis[bis(tri-termentioning
confidence: 67%
“…4). 35,38 Going down with the temperature we observed an upfield shift of cadmium resonance with the simultaneous broadening of the resonance signal in both presented spectra. However, we were not able to measure separate signals of A and B even at 90°C ( Fig.…”
Section: 5-dimethylpyridine) B and The Reaction Of Bis[bis(tri-termentioning
confidence: 67%
“…The geometry about each Cd(II) ion is heavily distorted from the ideal tetrahedral values, with a rather large N−Cd−N angle of 161°, probably because of the geometrical constraints imposed by the polymeric nature and periodicity restraints. Similar anomalous Cd(II) geometries, although rare, are not new: see for example the crystal structures of the mononuclear Cd(Pcy 3 ) 2 (2,6-F-phenolate) 2 and of the Cd(CH 3 ) 2 (dioxane) polymer, where angles up to 173.0° are found . The overall structure is polymeric and contains two-dimensional layers, stacked along b , of idealized p 2/ m 2/ c2 / a symmetry, interacting only through weak H···H van der Waals contacts.…”
Section: Resultsmentioning
confidence: 89%
“…2+ is the only thermodynamically stable species in this system. It is worth mentioning that all previously reported complexes of cadmium with phosphines contained only one or two coordinated phosphine ligands per Cd atom. Unfortunately, our attempts to isolate a solid product from this reaction failed. As a result of the quantitative examination of the 31 P and 113 Cd NMR signal line shapes in the frame of dynamic NMR techniques applied to chemical exchange, the chemical exchange rate constants ( k ) were estimated at various temperatures.…”
Section: Resultsmentioning
confidence: 93%
“…Extensive studies on the coordination of CdX 2 (X = Cl, Br, I, NCS, OR, SR, NO 3 , RCOO, RCS 2 ) with PR 3 (R = Ph, tolyl, Cy, Et, Bu, SiMe 3 ) and phospholes were carried out. The 1:1 and 1:2 complexes are typical products of such complexation. Few studies of the coordination of Cd 2+ to functionalized phosphines have been reported. Complexes with Ph 2 PC(S)NHPh and diphenylphosphinebenzenethiolate have been prepared. , The coordination of P(CH 2 COO) 3 3– and (OOCH 2 ) 2 PCH 2 CH 2 P(CH 2 COO) 2 4– with Cd 2+ leads to the formation of unique coordination polymers assembled through both Cd–P and Cd–O coordination. , In this paper, we report our study on the coordination of Cd 2+ with tris(hydroxymethyl)phosphine [P(CH 2 OH) 3 , THP] in methanol by 31 P and 111 Cd NMR at various temperatures.…”
Section: Introductionmentioning
confidence: 99%